2014
DOI: 10.1016/j.jbiomech.2014.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tissue properties, shape and orientation of microcalcifications on vulnerable cap stability using different hyperelastic constitutive models

Abstract: Approximately half of all cardiovascular deaths associated with acute coronary syndrome occur when the thin fibrous cap tissue overlying the necrotic core in a coronary vessel is torn, ripped or fissured under the action of high blood pressure. From a biomechanics point of view, the rupture of an atheroma is due to increased mechanical stresses in the lesion, in which the ultimate stress (i.e. peak circumferential stress (PCS) at failure) of the tissue is exceeded. Several factors including the cap thickness, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 27 publications
3
45
0
Order By: Relevance
“…A structural model with straightforward SEF (e.g., Holzapfel et al’s model) may be more efficient for FE simulations. Such SEFs have been employed in FE analysis for diseased coronary arteries (Holzapfel et al, 2005a; Cardoso et al, 2014). It noted that the two-layer models (accounts for individual layered microstructure) are typically used as the intima contributes negligible mechanical support for coronary arteries of normal animals, normal animals.…”
Section: Microstructure-based Mechanical Models Of Heathly Coronarymentioning
confidence: 99%
See 2 more Smart Citations
“…A structural model with straightforward SEF (e.g., Holzapfel et al’s model) may be more efficient for FE simulations. Such SEFs have been employed in FE analysis for diseased coronary arteries (Holzapfel et al, 2005a; Cardoso et al, 2014). It noted that the two-layer models (accounts for individual layered microstructure) are typically used as the intima contributes negligible mechanical support for coronary arteries of normal animals, normal animals.…”
Section: Microstructure-based Mechanical Models Of Heathly Coronarymentioning
confidence: 99%
“…The most widely used constitutive models are homogenous models due to their relatively simple SEF (Chau et al, 2004; Conway et al, 2012; García et al, 2012; Cardoso et al, 2014). The study of Imoto et al (Imoto et al, 2005) examined the longitudinal structural determinants of plaque vulnerability by linear elastic orthotropic models, and revealed that most common rupture point is that the shoulder of the fibrous cap.…”
Section: Finite Element Analyses Of Atherosclerosis Coronary Arteriesmentioning
confidence: 99%
See 1 more Smart Citation
“…In marked contrast, biomechanical analysis [7, 8] has shown that small microcalcifications (μCalcs) in close proximity within the fibrous cap itself can lead to a 200–700% increase in local tissue stresses [912]. Such a stress accumulation in a region of cap thinning is more than sufficient to exceed the local tissue threshold required to explain the asymptomatic rupture of non-stenotic plaque [714]. …”
Section: Introductionmentioning
confidence: 99%
“…Two distinct forms of cardiovascular calcification predominate clinically – atherosclerotic vascular calcification and calcific aortic valve disease (CAVD) (3, 4). Size and morphology determines the impact of calcification on these cardiovascular tissues (510). We recently showed that in pathologic conditions cells within atherosclerotic plaques release specialized extracellular vesicles (~100 nm) that nucleate calcium phosphate mineral (11, 12).…”
Section: Introductionmentioning
confidence: 99%